The nannies - Σκούρτης, Γιώργος, 1940- (Modern Greek Plays, 1995)
"The Nanies" first performed by Karolos Koun's Art Theater in 197, represents some of the best work done by Greek playwrights who emerged in the sixties and seventies. It is a play about a world where two people wait for a convenient solution to the hopelessness generated by a materialistic society devoid of the humanist vision, a solution that induces a dangerous hypnosis of the mind and creates a hysteria of acquisition culminating in violence and corruption.